Study of the challenges and opportunities of the commercialization of biodegradable packaging (2024)
The objective of the research is to know the degree of acceptance of biodegradable packaging in the city of Ipiales, Colombia. Where, the problem of pollution is understood from at a global, national and local level, and then delve into the commercialization of biodegradable packaging as a sustainable alternative. A survey was carried out on the population of Ipiales between 18 and 44 years old, which, according to DANE, corresponds to 54,296 inhabitants. The sample was obtained by applying a confidence level of 90% and a margin of error of 10%, for a total of 68 surveys.From the research it is concluded that the packaging would be well received by the population due to the growing interest in caring for the environment. However, for its commercialization, biodegradable packaging faces several challenges, highlighting the cost of manufacturing, the lack of information and the generation of environmental awareness.